COPULA METHOD IN PAIRS TRADING WITH SIMULATION OF COINTEGRATIED SERIES - Hans, Benedictus
Pairs trading is one of the stock investment strategies. This strategy uses two highly correlated stocks. A high correlation value indicates that both stocks tend to move together and have a long-term balance. In this final project, the amount of risk in the pairs trading strategy will be determined by the copula method. First, we will find a pair of cointegration and high correlated stock prices. Furthermore, it will be simulated for 5 years, as many as a thousand times the pair shares are cointegrated, correlated accordingly, and still inherit as much as possible the nature of the pair of shares previously obtained. And lastly, ther will be a copula method in pairs trading on each simulation result and calculate the VaR value and the total profit from each simulation result.